Internalized homophobia and rooted cosmopolitan identity in selected contemporary Indian diasporic fiction - Jeyasingam, Shobana (2021)
The challenges to contemporary cosmopolitanism with specific reference to marginalised communities is an area that has been shown to have a scarcity of literary study. Therefore, the present study is conducted to address this gap and highlight the problem of internalized homophobia among LGBTQ characters which is a deterrent to the construction of a cosmopolitan identity. The study is focused on migrant LGBTQ characters of the Indian diaspora in North America and how the presence of internalized homophobia deters the attainment of a cosmopolitan identity. Unearthing the challenges to becoming cosmopolitan due to internalized homophobia addresses the gap pertaining to LGBTQ narratives of the Indian Subcontinent whereby heteronormative traditions and beliefs of a homophobic environment that lead to the development of internalized homophobia deters LGBTQ characters from being autonomous and free despite being in a more accepting environment in a host country. Herein, this study first aims to examine the authors’ depiction of the cosmopolitan social setting in the host nation in providing acceptance for alternative sexual orientations in the selected novels. Moving on, the second objective is to investigate the patterns of internalized homophobia that manifest in the selected LGBTQ characters. Finally, the third objective aims to explicate the development of internalized homophobia and expound on the authors’ portrayal of internalized homophobia deterring the formation of a cosmopolitan identity in the selected LGBTQ characters. In doing so, this study utilizes textual analysis of the five selected novels, namely Rahul Mehta’s No Other World (2017), Mala Kumar’s The Paths of Marriage (2014), The Hungry Ghosts (2013) by Shyam Selvadurai, My Magical Palace (2012) by Kunal Mukherjee and Farzana Doctor’s Stealing Nasreen (2007) by combining the concepts of rooted cosmopolitanism by Kwame Anthony Appiah and internalized homophobia by Ilan H. Meyer and Laura Dean to anchor the conceptual framework. The current study is significant in its efforts to highlight the challenges to developing a cosmopolitan identity within cosmopolitan fiction of the Indian diaspora where previous research has mainly focused on ways to develop a cosmopolitan identity. This study concludes that societal conventions that are bred in heteronormativity are the root causes to internalized homophobia which in turn challenges the construction of a cosmopolitan identity. Therefore, future research could focus on fiction of other Asian diasporas who are also known for deep familial roots such as the Chinese, Koreans, or Japanese to determine the effects of internalized homophobia on the cosmopolitan values of the LGBTQ characters of Eastern Asian descent within a migrant background.